2020
DOI: 10.31234/osf.io/3xhk8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What Do Meditators Do When They Meditate? Proposing a Novel Basis for Future Meditation Research

Abstract: Meditation is an umbrella term for a vast range of contemplative practices. Former proposals have struggled to do justice to this diversity. To our knowledge, there is to date no comprehensive overview of meditation techniques spanning all major traditions. The present studies aimed at filling this gap. In a qualitative study, we compiled a collection of 309 meditation techniques through a literature search and interviews with 20 expert meditators. Then, we reduced this collection to 50 basic meditation techni… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…Alternatively, they could examine the effects of diverse meditation techniques in this context. Current research has revealed a multiplicity of meditation techniques (Matko and Sedlmeier, 2019 ; Matko et al, 2021b ), most of which are under researched at present. Furthermore, yoga incorporates a collection of diverse breathing techniques that can have quite different, sometimes even opposing effects on practitioners (Raghuraj et al, 1998 ; Peng et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, they could examine the effects of diverse meditation techniques in this context. Current research has revealed a multiplicity of meditation techniques (Matko and Sedlmeier, 2019 ; Matko et al, 2021b ), most of which are under researched at present. Furthermore, yoga incorporates a collection of diverse breathing techniques that can have quite different, sometimes even opposing effects on practitioners (Raghuraj et al, 1998 ; Peng et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Still, more research is necessary to understand thoroughly how each component contributes to the efficacy of combined treatments. Additionally, current research has demonstrated that Hindu and Buddhist meditators show very distinct preferences for specific meditation techniques (Matko et al, 2020). These differences between traditions might ultimately influence the outcomes of both related interventions and might account for the observed differences reviewed above.…”
Section: Discussionmentioning
confidence: 76%
“…This is usually cultivated through focused meditation, in which a particular object (e.g. the breath) is chosen as the target of attention (Matko et al, 2021;Matko & Sedlmeier, 2019). The practice of mindfulness has become popular in western cultures in the last years due to its putative health benefits (Kabat-Zinn, 2006).…”
Section: Introductionmentioning
confidence: 99%